Refractive change and incidence of myopia among rural Chinese children: the Handan Offspring Myopia Study. Issue 5 (13th January 2021) - Lin, Zhong; Vasudevan, Balamurali; Gao, Tieying; Zhou, Hongjia; Ciuffreda, Kenneth J; Liang, Yuanbo
Abstract : Purpose: To assess the refractive change and incidence of myopia, as well as their risk factors, among Chinese rural children aged 6–17 years. Methods: Children who completed the baseline vision examination of the Handan Offspring Myopia Study were re-examined, including both cycloplegic and non-cyloplegic autorefraction, with a mean follow-up time of 42.4±1.47 months. Results: A total of 601 children (68.5%) who completed both baseline and the follow-up examinations were enrolled. The cumulative refractive change and axial length change were −0.53±1.03 diopter and 0.39±0.46 mm (−0.15 diopter/year and 0.11 mm/year), respectively. A hundred and five out of the 469 non-myopic children at baseline become myopic at the follow-up, yielding a cumulative myopia incidence of 22.4% (95% CI: 18.6% to 26.2%), or annual myopia incidence of 6.3%. After adjustment, younger age (β=0.08, p<0.001), more myopic baseline refraction (β=0.31, p<0.001), larger difference between cycloplegic and non-cycloplegic refraction (β=−0.20, p=0.007) and more myopic paternal refraction (β=0.09, p=0.007) were found to be associated with more rapid myopic refractive change. More myopic baseline refraction (relative risk (RR), 95% CI: 0.19, 0.13–0.28, p<0.001) and more myopic paternal refraction (RR, 95% CI: 0.92, 0.84–1.00, p=0.039) were also associated with myopia incidence. Conclusion: Relatively low myopic refractive change and myopia incidence were found in this study cohort. Children's refraction and paternal refraction were associated with both myopic refractive change and myopia incidence. Such information will be helpful for further comparisons in other rural versus urban areas of China, and other countries.